Labeling “Introvert” pada Interaksi Sosial Peserta Didik Akselerasi Berbasis Pesantren (EDUKASIA, 2025)
This study examined the social dynamics of Smart Class Initiative (SCI) students within a pesantren-based education system at SMA Unggulan Haf-Sa Zainul Hasan BPPT Genggong Probolinggo. Drawing on Howard Gardner’s theory of multiple intelligences and the Indonesian Ministry of Education Regulation No. 12/2024 on gifted education, the research addressed common social challenges among excellent students, such as feelings of alienation and reduced peer interaction. Using a qualitative case study approach, data were gathered through in-depth interviews, participant observations at school and dormitory settings, and literature reviews. Data analysis followed the Miles and Huberman model and Johnny Saldana’s coding techniques. The findings revealed that SCI services did not create social gaps between SCI and regular students. Pesantren activities have encouraged active social engagement manifested through academic collaboration and mutual support. From Alfred Adler’s perspective, regular students’ feelings of inferiority stimulated positive social compensation reinforced by Islamic ukhuwah, resulting in an inclusive environment. The study highlighted the pesantren’s role as a mediator that has prevented introversion among excellent students. However, its single-site focus limits generalization, indicating the need for future comparative research.